<span>A = {odd numbers between 0 and 100}
</span><span>A = {1, 3, 5, 7,...., 95, 97, 99}
B = </span><span>{numbers between 50 and 150 that are evenly divisible by 5}
B = {50, 55, 60, 65, ..., 140, 145, 150}
The notation </span><span>A ∩ B means the set of items that are in set A and also in set B. In terms of venn diagrams, it's the overlapping region between circle A and circle B
In this case, the following values are found in both set A and set B
{55, 65, 75, 85, 95}
So that's why
</span>A ∩ B = <span>{55, 65, 75, 85, 95}
which is the final answer</span>
Is this for area and perimeter? If so, first make the fraction a decimal, (that would be 3.5). Then, for permeter, add 3.5 + 3.5 + 9 + 9, which is 25, for area, multiply 3.5 by 9, which is 31.5. Hope this helped!
Answer:
Step-by-step explanation:
Remember that the formula to get the area of a right triangle is base times height divided by 2, so to find the area:
5 x 12 = 60/2 = 30
Area of this triangle is 30.
To find the perimeter, add all the sides:
5 + 12 + 13 = 30.
Perimeter of this triangle is 30.
8/x+9-(2/x-3)=0
Step by step solution :
Step 1 :
2
Simplify —
x
Equation at the end of step 1 :
8 2
(— + 9) - (— - 3) = 0
x x
Step 2 :
Rewriting the whole as an Equivalent Fraction :
2.1 Subtracting a whole from a fraction
Rewrite the whole as a fraction using x as the denominator :
3 3 • x
3 = — = —————
1 x
Equivalent fraction : The fraction thus generated looks different but has the same value as the whole
Common denominator : The equivalent fraction and the other fraction involved in the calculation share the same denominator
Adding fractions that have a common denominator :
2.2 Adding up the two equivalent fractions
Add the two equivalent fractions which now have a common denominator
Combine the numerators together, put the sum or difference over the common denominator then reduce to lowest terms if possible:
2 - (3 • x) 2 - 3x
——————————— = ——————
x x
Equation at the end of step 2 :
8 (2 - 3x)
(— + 9) - ———————— = 0
x x
Step 3 :
8
Simplify —
x
Equation at the end of step 3 :
8 (2 - 3x)
(— + 9) - ———————— = 0
x x
Step 4 :
Rewriting the whole as an Equivalent Fraction :
4.1 Adding a whole to a fraction
Rewrite the whole as a fraction using x as the denominator :
9 9 • x
9 = — = —————
1 x
Adding fractions that have a common denominator :
4.2 Adding up the two equivalent fractions
8 + 9 • x 9x + 8
————————— = ——————
x x
Equation at the end of step 4 :
(9x + 8) (2 - 3x)
———————— - ———————— = 0
x x
Step 5 :
Adding fractions which have a common denominator :
5.1 Adding fractions which have a common denominator
Combine the numerators together, put the sum or difference over the common denominator then reduce to lowest terms if possible:
(9x+8) - ((2-3x)) 12x + 6
————————————————— = ———————
x x
Step 6 :
Pulling out like terms :
6.1 Pull out like factors :
12x + 6 = 6 • (2x + 1)
Equation at the end of step 6 :
6 • (2x + 1)
———————————— = 0
x
Step 7 :
When a fraction equals zero :
7.1 When a fraction equals zero ...
Where a fraction equals zero, its numerator, the part which is above the fraction line, must equal zero.
Now,to get rid of the denominator, Tiger multiplys both sides of the equation by the denominator.
Here's how:
6•(2x+1)
———————— • x = 0 • x
x
Now, on the left hand side, the x cancels out the denominator, while, on the right hand side, zero times anything is still zero.
The equation now takes the shape :
6 • (2x+1) = 0
Equations which are never true :
7.2 Solve : 6 = 0
This equation has no solution.
A a non-zero constant never equals zero.